2015
DOI: 10.1371/journal.pone.0130788
|View full text |Cite
|
Sign up to set email alerts
|

Insect Antimicrobial Peptide Complexes Prevent Resistance Development in Bacteria

Abstract: In recent decades much attention has been paid to antimicrobial peptides (AMPs) as natural antibiotics, which are presumably protected from resistance development in bacteria. However, experimental evolution studies have revealed prompt resistance increase in bacteria to any individual AMP tested. Here we demonstrate that naturally occurring compounds containing insect AMP complexes have clear advantage over individual peptide and small molecule antibiotics in respect of drug resistance development. As a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 32 publications
5
61
0
Order By: Relevance
“…The respective microorganisms readily developed bacterial resistance to the reference antibiotics, whereas no signs of resistance to the extracted AMP compound were observed. Similar results were obtained by Chernysh et al (2015) for AMP compounds isolated from the maggots of 3 other fly species, e.g., blue blowfly (Calliphora vomitoria), green bottleneck fly (Lucilia sericata) and house fly (M. domestica).…”
Section: Bacterial Resistance To Insect Ampssupporting
confidence: 80%
See 3 more Smart Citations
“…The respective microorganisms readily developed bacterial resistance to the reference antibiotics, whereas no signs of resistance to the extracted AMP compound were observed. Similar results were obtained by Chernysh et al (2015) for AMP compounds isolated from the maggots of 3 other fly species, e.g., blue blowfly (Calliphora vomitoria), green bottleneck fly (Lucilia sericata) and house fly (M. domestica).…”
Section: Bacterial Resistance To Insect Ampssupporting
confidence: 80%
“…Results obtainened in vitro suggest that compounds containing insect AMP complexes have an advantage over individual peptide and small molecule antibiotics (Chernysh et al, 2015). In line with this, the application of insect meal providing a variety of different AMPs as a supplement to animal feed may give rise to new possibilities in animal production.…”
Section: Dietary Supplementation Of Insect Ampsmentioning
confidence: 76%
See 2 more Smart Citations
“…However, several studies have shown that AMPs have no real advantage compared with traditional antibiotics [16][17][18] . In recent years, AMPs have been used as a feed additive to prevent S. Pullorum infection.…”
Section: Introductionmentioning
confidence: 99%